(untitled) (NAU Journal of Technology and Vocational Education, 2024)
Technical colleges in Nigeria were established to train skilled craftsmen, technicians, and personnel who will be innovative, inventive, and self-reliant. This study investigated the effect of reflective inquiry instructional strategy on students’ practical skills in electrical installation and maintenance works in technical colleges in Delta State, Nigeria. The study was quasi-experimental and used a pre-test, post-test, non-randomized group design. Two research questions guided the study, while two null hypotheses were tested at 0.5 level of significance. The population of the study consisted of 138 Vocation 2 students, while the sample size was 93 Vocation 2 students drawn through multiple random sampling techniques. A validated Electrical Installation and Maintenance Works Test (EIMWT) of surface house wiring, conduit house wiring, and trunking systems with a rating scale containing 25 items was used for data collection. The reliability of the instrument was determined by administering it to a group of 20 students who were not part of the study sample. The scores of the different ratters were correlated using the Kendell coefficient of concordance with the help of the Statistical Package for Social Sciences (SPSS). A reliability coefficient of 0.9 was obtained. The arithmetic mean was used to analyse the data with respect to the research questions, while ANCOVA was used to test the hypotheses. Findings indicated that students taught with RIIS obtained a higher mean than those in the control group, and female students taught with RIIS performed better than male students; therefore, the use of RIIS in teaching electrical installation and maintenance works is significant. The implication is that reflective inquiry instructional strategies improve students’ achievement in electrical installation and maintenance work. Consequently, it was recommended that technical teachers in technical colleges adopt reflective inquiry instructional strategies to improve students’ academic achievement in practical skills in electrical installation and maintenance work.